Regional‐Scale Low‐Angle Normal Fault Friction and Cohesion Constrained From Mohr‐Coulomb Models of Active and Abandoned Range‐Front Faults in Papua New Guinea. Issue 4 (20th April 2022) - Webber, Samuel; Little, Timothy; Boulton, Carolyn; Biemiller, James; Mizera, Marcel
Abstract: Low‐angle normal faults (LANFs) are poorly understood, as their slip at <30° dips appears inconsistent with Byerlee friction and Andersonian stresses. Rider blocks are fault slices formed when the uppermost part of a LANF is abandoned in favor of a new, steeper fault. Mohr‐Coulomb modeling of rider blocks can constrain fault frictional and cohesive strength provided known fault geometries. Analytical modeling shows that LANF viability depends on fault geometry and on the frictional and cohesive strength of the fault relative to that of the surrounding crust. Modeling of the Gwoira rider block, located atop the Mai'iu LANF, southeastern Papua New Guinea, indicates that this fault segment is frictionally weak (0.04 ≤ µ f ≤ 0.17) in the shallow crust, with neither non‐Andersonian stresses nor supra‐hydrostatic fluid pressures required. Such weakness favors slip localization onto a single fault, enabling rapid slip rates at shallow dips. We show that slip at a second site, which lacks a rider block, does not require a weak fault because of a large fault/crust cohesion contrast and a rapid steepening of dip on the convex‐upward fault from only 21° at the surface to >30° down‐dip. From our results, we characterize four possible styles of faulting on convex‐up normal faults: (a) total fault slip, (b) footwall damage, (c) fault partial abandonment, and (d) total fault abandonment. Our results reveal that LANF faulting style depends on the strength of the fault compared to the surrounding crust, fault geometry, and the distribution of differential stress required for slip as a function of depth. Plain Language Summary: Normal faults are fractures that accommodate extension in regions where tectonic plates pull apart. They are usually inclined at steep angles; however, some are oriented at shallow angles that are unfavorable for slip (<30°)—so‐called low‐angle normal faults (LANFs). LANFs may slip due to low frictional strengths, as suggested by laboratory testing of samples obtained from these faults. However, such experiments are performed on small samples, so their applicability at kilometer scales is questionable. The Gwoira rider block is a slice of sedimentary rock, bounded below by an inactive fault (the Mai'iu fault), and above by an active fault (the Gwoira fault). Using the geometries of these faults, we constrain their frictional and cohesive strengths. The results suggest that the Mai'iu fault is weak at one location where it dips <20° at the surface, but not necessarily at other locations where it steepens down dip to >30°. Other possible explanations for how these faults slip—elevated fluid pressures within the fault, or that the local stress field is oriented at unusual angles—are not required. Our results also delineate four main ways in which LANFs can slip, depending on their shape and fault strength compared to that of the surrounding rock. Key Points: Applying Mohr‐Coulomb mechanics to a rider block, we show that part of the fault slips with a friction coefficient of <0.17 Non‐Andersonian stresses and supra‐hydrostatic fluid pressures are not required for continued slip on convex‐upward low‐angle normal faults Four failure modes are possible for curved normal faults, controlled by fault dip and fault strength compared to the surrounding crust